Technical nuances of commonly used vascularised flaps for skull base reconstruction - I P, Tang; R L, Carrau; B A, Otto; D M, Prevedello; P, Kasemsiri; L, Ditzel; J, Muto; B, Kapucu; C, Kircsh (Journal of Laryngology & Otology, 2015)
Background and Methods: Reconstruction with a vascularised flap provides the most reliable outcome, with postoperative cerebrospinal fluid leak rates of less than 5 per cent. This article aims to review and summarise the critical technical aspects of the vascularised flaps most commonly used for skull base reconstruction. Results: Vascularised flaps are classified as intranasal or extranasal. The intranasal group includes the Hadad–Bassagaisteguy nasoseptal flap, the Caicedo reverse nasoseptal flap, the nasoseptal rescue flap, the posteriorly or anteriorly based lateral wall flaps, and the middle turbinate flap. Extranasal flaps include the transfrontal pericranial and transpterygoid temporoparietal flaps. Conclusion: The Hadad–Bassagaisteguy nasoseptal flap is overwhelmingly favoured for reconstructing extensive defects of anterior, middle and posterior cranial base. Its pertinent technical features are described. However, it is essential to master the skills required for the various extranasal or regional vascularised flaps because each can offer a reconstructive alternative for specific patients, especially when open approaches are needed and/or intranasal vascularised flaps are not feasible.